Transparent electromagnetic shielding metal copper mesh and preparation method and application thereof

The manufacturing process of transparent electromagnetic shielded metal copper grids is simplified through femtosecond laser reduction direct writing method, solving the problems of complex processes and high costs in the existing technology, achieving efficient and low-cost manufacturing, and improving shielding efficiency and light transmittance.

CN119855124AActive Publication Date: 2025-04-18BEIJING UNIV OF TECH

Patent Information

Application Number
CN202510110087.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-23
Publication Date
2025-04-18
Estimated Expiration
2045-01-23

AI Technical Summary

Technical Problem

The existing technical process for manufacturing transparent electromagnetic shielded metal grids is complex, difficult to process and high manufacturing costs, making it difficult to meet the efficient and low-cost manufacturing needs.

Method used

A transparent electromagnetic shielded metal copper grid was prepared by femtosecond laser reduction direct writing method. By applying an ink layer on the electromagnetic shielding substrate, and using femtosecond laser to convert the ink into a metal copper grid, and finally, the ink that has not been converted into a metal grid was cleaned with a cleaning solution.

Benefits of technology

It realizes efficient and low-cost manufacturing of transparent electromagnetic shielded metal copper grids, simplifies the process, improves shielding efficiency and light transmittance, and enhances the conductivity and magnetic permeability of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119855124A_ABST
    Figure CN119855124A_ABST
Patent Text Reader

Abstract

The invention provides a transparent electromagnetic shielding metal copper mesh and a preparation method and application thereof. The preparation method of the transparent electromagnetic shielding metal copper mesh comprises the steps that an electromagnetic shielding substrate is coated with an ink layer, then the ink layer is converted into a patterned metal copper mesh to be deposited on the surface of the electromagnetic shielding substrate through a femtosecond laser reduction direct writing method, and finally ink which is not converted into the metal mesh is cleaned through cleaning liquid. Obtaining a transparent electromagnetic shielding metal copper mesh; the ink is prepared from copper salt, water, reductive low-carbon alcohol and a nano material, and the nano material comprises at least one of a high-conductivity nano material and a high-permeability nano material. According to the method, the transparent electromagnetic shielding metal copper mesh is prepared through femtosecond laser reduction direct writing, by adjusting the line width and the period of the metal copper mesh, the shielding effectiveness is effectively improved under the condition that the high light transmittance of an electromagnetic shielding material is guaranteed, the technological method is simple and feasible, and high-efficiency and low-cost manufacturing of the transparent electromagnetic shielding metal copper mesh is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of laser direct writing, and in particular to a transparent electromagnetic shielding metal copper grid and a preparation method and application thereof. Background Art

[0002] With the popularization of electronic devices and wireless communication technology, electromagnetic radiation is everywhere in life. In the field of national defense and aerospace, the development of electronic warfare and radar stealth technology has put forward extremely high requirements on electromagnetic shielding materials for the shielding and anti-interference of key equipment and communication systems. Especially in high-density electronic equipment environments, mutual interference between devices may cause performance degradation or equipment failure. At the same time, high optical transparency needs to be ensured in specific areas such as touch screens, displays, and aircraft cockpits. Therefore, the design and development of transparent electromagnetic shielding materials has become a key technology to reduce the impact of electromagnetic radiation.

[0003] Metal mesh electromagnetic shielding material is a material that blocks or reflects electromagnetic waves to reduce their impact. Compared with other types of electromagnetic shielding materials, metal mesh has the characteristics of high conductivity, which can effectively reflect electromagnetic waves and reduce the penetration of electromagnetic waves. At the same time, the structural design of the mesh can shield electromagnetic waves in multiple frequency bands and remain transparent in the visible light band. It can be seen that the period, line width and material properties of the metal mesh are important parameters that affect the shielding effectiveness.

[0004] Existing manufacturing technologies mainly use photolithography-based metal grid manufacturing technologies, such as metal nanomaterial sintering, selective electrodeposition, magnetron sputtering, metal evaporation, etc., to shield electromagnetic waves by preparing a conductive micron or nanometer metal grid on the surface of a transparent substrate, while the fine structure of the grid allows visible light to pass through. The above manufacturing process includes coating photoresist, photomask exposure, development, metal deposition, photoresist removal, etc. When applied on a large area, the process is complicated, the processing is difficult, and the manufacturing cost is high. Summary of the invention

[0005] The present invention aims to solve one of the technical problems in the prior art at least to a certain extent. To this end, one object of the present invention is to provide a transparent electromagnetic shielding metal copper grid and a preparation method and application thereof.

[0006] In a first aspect of the present invention, a method for preparing a transparent electromagnetic shielding metal copper grid by femtosecond laser reduction direct writing is provided, the method comprising: An ink layer is coated on an electromagnetic shielding substrate, and then a femtosecond laser reduction direct writing method is used to transform the ink layer into a patterned metal copper grid deposited on the surface of the electromagnetic shielding substrate, and finally the ink that has not been transformed into a metal grid is cleaned with a cleaning liquid to obtain a transparent electromagnetic shielding metal copper grid; The raw materials for preparing the ink include copper salt, water, reducing low-carbon alcohol and nanomaterials, and the nanomaterials include at least one of high-conductivity nanomaterials and high-magnetic permeability nanomaterials.

[0007] According to the method for preparing transparent electromagnetic shielding metal copper grid by femtosecond laser reduction direct writing provided by the present invention, the high-energy focused laser beam of the femtosecond laser is used to reduce the metal ions on the surface of the substrate and form the metal directly on the surface of the substrate. The femtosecond laser method does not require the use of a mask, and only greatly simplifies the manufacturing process by adjusting the laser scanning path. At the same time, the highly focused spot of the femtosecond laser can realize the manufacture of micrometer or even nanometer scale metal grids, which not only ensures transparency in the visible light band, but also meets the needs of electromagnetic shielding in different frequency bands. Specifically, the femtosecond laser method can balance high transmittance and shielding effectiveness, and accurately control the line width, period and thickness of the metal grid by designing and optimizing the laser scanning path and laser processing parameters, so as to achieve effective electromagnetic shielding while maintaining high transmittance. On the other hand, the present invention uses the above-mentioned ink to prepare the metal copper grid, so that the femtosecond laser can prepare the high-precision metal grid, and further optimize the performance of the electromagnetic shielding material. Specifically, by adding nanomaterials to the ink, the conductivity and / or magnetic permeability of the metal grid can be enhanced, thereby improving the electromagnetic shielding effect of the metal copper grid.

[0008] According to the method for preparing a transparent electromagnetic shielding metal copper grid by femtosecond laser reduction direct writing provided by the present invention, the line width of the transparent electromagnetic shielding metal copper grid is 10-50 μm, and the period is 10-150 μm, preferably the line width is 20-40 μm, and the period is 60-120 μm. When the line width and period of the transparent electromagnetic shielding metal copper grid are within the above range, the electromagnetic shielding effect of the transparent electromagnetic shielding metal copper grid is improved while ensuring good light transmittance of the metal copper grid.

[0009] According to the method for preparing a transparent electromagnetic shielding metal copper grid by femtosecond laser reduction direct writing provided by the present invention, the transparent electromagnetic shielding metal copper grid has a thickness of 5-15 μm.

[0010] It should be noted that the present invention does not specifically limit the specific shape of the metal copper grid. For example, it can be a rectangular metal grid (such as Figure 2 As shown), it can also be a diamond metal grid, or a triangular metal grid (such as Figure 4 shown) etc.

[0011] According to the method for preparing transparent electromagnetic shielding metal copper grid by femtosecond laser reduction direct writing provided by the present invention, the process parameters of the femtosecond laser reduction direct writing method include: the central pulse width of the femtosecond laser is 10 -15 -10 -12s, laser wavelength is 500-1100 nm, pulse repetition frequency is 100 kHz-1 MHz, laser power is 0.5-8 W, spot diameter is 10-300 μm, and spot moving speed is 1-500 mm / s. Using the above femtosecond laser process parameters, a metal copper grid with suitable line width, period and thickness can be prepared, thereby improving the electromagnetic shielding effect and transmittance of the transparent electromagnetic shielding metal copper grid.

[0012] In some embodiments of the present invention, the electromagnetic shielding substrate includes one of quartz, glass, polyethylene terephthalate film, polycarbonate, and polyimide film.

[0013] In some embodiments of the present invention, the high-conductivity nanomaterial is selected from at least one of graphite, carbon powder, and metallic silver. Selecting the above substances as high-conductivity nanomaterials can enhance the conductivity of the metallic copper grid.

[0014] In some embodiments of the present invention, the high magnetic permeability nanomaterial is selected from at least one of ferroferric oxide, spinel ferrite, cobalt oxide, and metallic nickel. Selecting the above substances as high magnetic permeability nanomaterials can enhance the magnetic permeability of the metal copper grid, thereby improving the electromagnetic shielding effect of the metal copper grid.

[0015] According to the method for preparing a transparent electromagnetic shielding metal copper grid by femtosecond laser reduction direct writing provided by the present invention, the reducing low-carbon alcohol is selected from at least one of methanol, ethylene glycol, propylene glycol and glycerol.

[0016] In some embodiments of the present invention, the copper salt is selected from at least one of copper chloride, copper nitrate and copper formate.

[0017] In some embodiments of the present invention, the volume ratio of water to reducing low-carbon alcohol is 1: (3-6). Controlling the volume ratio of water to reducing low-carbon alcohol within the above range can ensure the reducing ability of the material system, while effectively dissolving metal salts and maintaining the diffusion ability of metal ions.

[0018] In some embodiments of the present invention, the mass ratio of water to copper salt is 1: (1-10). Controlling the mass ratio of water to copper salt within the above range can effectively dissolve metal salts, release metal ions into the solution to participate in the reaction, and avoid the inability of metal ions to nucleate due to too low concentration or insufficient solvent to cause incomplete dissolution of metal salts.

[0019] In some embodiments of the present invention, the mass ratio of the nano material to the copper salt is 1: (1-100). Controlling the mass ratio of the nano material to the copper salt within the above range can enhance the electrical conductivity and / or magnetic permeability of the shielding material, thereby improving the electromagnetic shielding effect of the metal copper grid.

[0020] In some embodiments of the present invention, the diameter of the nanomaterial is 20-100 nm. By controlling the diameter of the nanomaterial within the above range, the nanomaterial can be evenly dispersed and the serious agglomeration caused by excessive surface energy of the nanomaterial or precipitation caused by excessive density can be avoided.

[0021] According to the method for preparing a transparent electromagnetic shielding metal copper grid by femtosecond laser reduction direct writing provided by the present invention, the preparation method of the ink comprises: dissolving the copper salt in a mixed solvent of the water and the reducing low-carbon alcohol and heating and stirring, then adding the nanomaterial and mixing and stirring, and then heating to remove water. First, the copper salt is dissolved in a mixed solvent of water and the reducing low-carbon alcohol and heated and stirred, and the copper salt and water are fully reacted by heating and stirring to obtain a basic copper salt, and then the basic copper salt and the nanomaterial are mixed and stirred to fully disperse the nanomaterial in the solution, and finally heated to remove water, so as to obtain an ink for preparing a transparent electromagnetic shielding metal copper grid.

[0022] In some embodiments of the present invention, the temperature of the heating and stirring is 170-190°C, and the time is 10 min-2h. By controlling the temperature and time of the heating and stirring within the above range, the copper salt and water can react fully to obtain basic copper salt, thereby achieving femtosecond laser direct writing to obtain a transparent electromagnetic shielding metal copper grid.

[0023] In some embodiments of the present invention, the heating temperature for removing water by heating is 70-120° C., and the heating time is 2-24 h.

[0024] In a second aspect of the present invention, a transparent electromagnetic shielding metal copper grid is provided, and the metal copper grid is prepared by the above method, so that the metal copper grid has excellent electromagnetic shielding performance and good light transmittance.

[0025] In a third aspect of the present invention, the present invention proposes the application of the above-mentioned transparent electromagnetic shielding metal copper grid in the field of electronic radar shielding.

[0026] The present invention at least includes the following technical effects: (1) The present invention utilizes a femtosecond laser reduction direct writing method to prepare a transparent electromagnetic shielding metal copper mesh, which has the characteristics of high flexibility, high adaptability, and no need for a mask, thereby achieving high-efficiency and low-cost manufacturing of a transparent electromagnetic shielding metal copper mesh.

[0027] (2) The present invention effectively improves the shielding effectiveness by adjusting the line width and period of the metal copper grid while ensuring the high transmittance of the electromagnetic shielding material. The process method is simple and feasible. In addition, the ink for preparing the metal copper grid of the present invention can further enhance the electrical conductivity and / or magnetic permeability of the material while ensuring the high conductivity of the metal copper grid, thereby effectively improving the electromagnetic shielding effectiveness of the metal copper grid. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0029] Figure 1 This is a physical picture of the ink provided in Example 1 of the present invention; Figure 2 is a diagram of the structure of a metal copper grid provided in Example 1 of the present invention; Figure 3 This is a physical picture of the metal copper grid provided in Example 1 of the present invention; Figure 4 It is a metal copper grid structure diagram of an embodiment of the present invention. DETAILED DESCRIPTION

[0030] Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. The present invention is described below with reference to specific embodiments. It should be noted that these embodiments are merely illustrative and do not limit the present invention in any way.

[0031] Example 1 (1) Measure 6 mL of ethylene glycol and 1.5 mL of deionized water and mix them evenly as a mixed solvent. Weigh 4 g of copper nitrate and add it to the mixed solvent to completely dissolve it to obtain a copper ion solution. (2) heating the copper ion solution to 170° C. for 25 min, until bubbles are generated in the solution and yellow-brown gas is released, cooling the solution to room temperature to obtain a basic copper nitrate dispersion; (3) Weigh 50 mg of graphene (graphene flake diameter is 30 nm-40 nm) and add it to basic copper nitrate dispersion. Place the mixed liquid in an ultrasonic oscillator with a frequency of 40 kHz and oscillate for 2 h to obtain a uniformly dispersed suspension. (4) placing the suspension on a magnetic stirring platform with a heating function, setting the temperature to 120°C, setting the magnetic speed to 1000 r / min, and heating for 12 h to finally obtain copper ion ink; (5) Scrape the ink onto the surface of the polyimide film to form a uniform film; (6) Set the metal grid line width to 30 μm, the grid period to 200 μm, adjust the focus spot diameter to 30 μm, and set the scanning path to move linearly along the periodic grid; (7) A femtosecond laser with a wavelength of 1030 nm, a pulse width of 100 fs, and a repetition rate of 100 kHz was used to reduce copper ion ink and directly write a metal copper grid. The laser power was 3.5 W, the spot diameter was 40 μm, and the scanning speed was 300 mm / s. After processing, the excess metal ion membrane was rinsed off with deionized water and ethanol, and then dried with compressed air.

[0032] in, Figure 1 This is a physical picture of the ink used in Example 1; Figure 2 is the metal grid structure designed in Example 1, Figure 3 This is a real picture of the manufactured metal copper mesh. The electromagnetic shielding effectiveness of the metal copper mesh is >30 dB at 8-12 GHz.

[0033] Example 2 (1) Measure 6 mL of ethylene glycol and 1.5 mL of deionized water and mix them evenly as a mixed solvent. Weigh 4 g of copper nitrate and add it to the mixed solvent to completely dissolve it to obtain a copper ion solution. (2) heating the copper ion solution to 170° C. for 25 min, until bubbles are generated in the solution and yellow-brown gas is released, cooling the solution to room temperature to obtain a basic copper nitrate dispersion; (3) Weigh 50 mg of graphene (graphene flake diameter is 30 nm-40 nm) and add it to basic copper nitrate dispersion. Place the mixed liquid in an ultrasonic oscillator with a frequency of 40 kHz and oscillate for 2 h to obtain a uniformly dispersed suspension. (4) placing the suspension on a magnetic stirring platform with a heating function, setting the temperature to 120°C, setting the magnetic speed to 1000 r / min, and heating for 12 h to finally obtain copper ion ink; (5) Scrape the ink onto the surface of the polyimide film to form a uniform film; (6) Set the metal grid line width to 30 μm, the grid period to 400 μm, adjust the focus spot diameter to 30 μm, and set the scanning path to move linearly along the periodic grid; (7) A femtosecond laser with a wavelength of 1030 nm, a pulse width of 100 fs, and a repetition rate of 100 kHz was used to reduce copper ion ink and directly write a metal copper grid. The laser power was 3.5 W, the spot diameter was 40 μm, and the scanning speed was 300 mm / s. After processing, the excess metal ion membrane was rinsed off with deionized water and ethanol, and then dried with compressed air.

[0034] Among them, the electromagnetic shielding effectiveness of metal copper mesh is >20 dB at 8-12 GHz.

[0035] Comparative Example 1 (1) Measure 6 mL of ethylene glycol and 1.5 mL of deionized water and mix them evenly as a mixed solvent. Weigh 4 g of copper nitrate and add it to the mixed solvent to completely dissolve it to obtain a copper ion solution. (2) heating the copper ion solution to 170° C. for 25 min, until bubbles are generated in the solution and yellow-brown gas is released, cooling the solution to room temperature to obtain a basic copper nitrate dispersion; (3) placing the basic copper nitrate dispersion on a magnetic stirring platform with a heating function, setting the temperature to 120°C, setting the magnetic speed to 1000 r / min, and heating for 12 h to finally obtain copper ion ink; (4) Scrape the ink onto the surface of the polyimide film to form a uniform film; (5) Set the metal grid line width to 30 μm, the grid period to 100 μm, adjust the focus spot diameter to 30 μm, and set the scanning path to move linearly along the periodic grid; (6) A femtosecond laser with a wavelength of 1030 nm, a pulse width of 100 fs, and a repetition rate of 100 kHz was used to reduce copper ion ink and directly write a metal copper grid. The laser power was 3.5 W, the spot diameter was 40 μm, and the scanning speed was 300 mm / s.

[0036] Due to the lack of nanomaterials in the ink, the femtosecond laser processing area lacks non-uniform nucleation sites for metal atoms. At the same time, compared with the ink containing nanomaterials, the main substance that absorbs laser energy in the ink in Comparative Example 1 is metal ions, which leads to too high penetration depth of the light beam in the ink, too dispersed laser energy, and unable to meet the temperature required for metal ion reduction. Therefore, the ink used in Comparative Example 1 cannot form a metal grid.

[0037] Comparative Example 2 (1) Measure 6 mL of ethylene glycol and 1.5 mL of deionized water and mix them evenly as a mixed solvent. Weigh 4 g of copper nitrate and add it to the mixed solvent to completely dissolve it to obtain a copper ion solution. (2) Weigh 50 mg of graphene and add it to the copper ion solution. Place the mixed liquid in an ultrasonic oscillator with a frequency of 40 kHz and oscillate for 2 h to obtain a uniformly dispersed suspension. (3) placing the suspension on a magnetic stirring platform with a heating function, setting the temperature to 120°C, setting the magnetic speed to 1000 r / min, and heating for 12 h to finally obtain copper ion ink; (4) Scrape the ink onto the surface of the polyimide film to form a uniform film; (5) Set the metal grid line width to 30 μm, the grid period to 100 μm, adjust the focus spot diameter to 30 μm, and set the scanning path to move linearly along the periodic grid; (6) A femtosecond laser with a wavelength of 1030 nm, a pulse width of 100 fs, and a repetition rate of 100 kHz was used to reduce copper ion ink and directly write a metal copper grid. The laser power was 3.5 W, the spot diameter was 40 μm, and the scanning speed was 300 mm / s.

[0038] Since the ink process lacks the important steps of heating and stirring to prepare basic copper salts, the ink contains acid salts that are completely dissolved in the solvent, and the strong acid radicals have strong oxidizing properties. Compared with strong acid and weak base salts, basic salts are less stable and are more easily decomposed into intermediate products and reduced to metal elements under the action of laser heating and reducing solvents. Therefore, the ink used in Comparative Example 2 also cannot prepare a metal copper grid.

[0039] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a transparent electromagnetic shielding metal copper grid by femtosecond laser reduction direct writing, characterized in that: include: An ink layer is coated on an electromagnetic shielding substrate, and then a femtosecond laser reduction direct writing method is used to transform the ink layer into a patterned metal copper grid deposited on the surface of the electromagnetic shielding substrate, and finally the ink that has not been transformed into a metal grid is cleaned with a cleaning liquid to obtain a transparent electromagnetic shielding metal copper grid; The raw materials for preparing the ink include copper salt, water, reducing low-carbon alcohol and nanomaterials, and the nanomaterials include at least one of high-conductivity nanomaterials and high-magnetic permeability nanomaterials.

2. The method according to claim 1, characterized in that: The transparent electromagnetic shielding metal copper grid has a line width of 10-50 μm and a period of 10-150 μm, preferably a line width of 20-40 μm and a period of 60-120 μm; And / or, the transparent electromagnetic shielding metal copper grid has a thickness of 5-15 μm.

3. The method according to claim 1 or 2, characterized in that: The process parameters of the femtosecond laser reduction direct writing method include: the femtosecond laser center pulse width is 10 -15 -10 -12 s, laser wavelength is 500-1100 nm, pulse repetition frequency is 100 kHz-1 MHz, laser power is 0.5-8 W, spot diameter is 10-300 μm, and spot moving speed is 1-500 mm / s; And / or, the electromagnetic shielding substrate includes one of quartz, glass, polyethylene terephthalate film, polycarbonate, and polyimide film.

4. The method according to claim 1, characterized in that: The high conductivity nanomaterial is selected from at least one of graphite, carbon powder, and metallic silver; And / or, the high magnetic permeability nanomaterial is selected from at least one of ferroferric oxide, spinel ferrite, cobalt oxide, and metallic nickel; And / or, the reducing low-carbon alcohol is selected from at least one of methanol, ethylene glycol, propylene glycol and glycerol; And / or, the copper salt is selected from at least one of copper chloride, copper nitrate and copper formate.

5. The method according to claim 1 or 4, characterized in that: The volume ratio of the water to the reducing low-carbon alcohol is 1:(3-6); And / or, the mass ratio of the water to the copper salt is 1:(1-10).

6. The method according to claim 1 or 4, characterized in that: The mass ratio of the nano material to the copper salt is 1:(1-100); And / or, the nanomaterial has a diameter of 20-100 nm.

7. The method according to claim 1 or 4, characterized in that: The ink preparation method comprises: dissolving the copper salt in a mixed solvent of the water and the reducing low-carbon alcohol, heating and stirring, then adding the nano material, mixing and stirring, and then heating to remove water.

8. The method according to claim 7, characterized in that: The heating and stirring temperature is 170-190°C and the time is 10min-2h; And / or, the heating temperature for removing water by heating is 70-120°C, and the heating time is 2-24 h.

9. A transparent electromagnetic shielding metal copper grid, characterized in that: The method is prepared by any one of claims 1 to 8.

10. Application of the transparent electromagnetic shielding metal copper grid according to claim 9 in the field of electronic radar shielding.

Citation Information

Patent Citations

  • Manufacturing method of metal mesh conducting film, metal mesh conducting film and touch panel

    CN104750311A

  • Method for preparing transparent conducting thin film by printing and chemical reduction method

    CN109686502A

  • Multi-layer metal net grid electromagnetic shielding optical window employing femtosecond laser etching and fabrication method thereof

    CN109769387A

  • Nano-silver / graphene composite electromagnetic shielding ink and preparation method thereof

    CN111560188A

  • Method for manufacturing metal microstructure through high repetition frequency ultrafast laser efficient direct writing

    CN112517922A

Cited By

  • Electromagnetic shielding material and preparation method and application thereof

    CN121586249A

  • Method for improving density of laser direct writing flexible copper circuit

    CN121908473A